2004
DOI: 10.1111/j.0022-202x.2004.22417.x
|View full text |Cite
|
Sign up to set email alerts
|

Type II Collagen Accumulation in Overlying Dermo-Epidermal Junction of Pilomatricoma Is Mediated by Bone Morphogenetic Protein 2 and 4

Abstract: Pilomatricoma consists of the cells differentiating towards hair matrix cells. Immunohistochemical study revealed the deposition of type II collagen in the overlying dermo-epidermal junction (DEJ) of this benign tumor. Proalpha(1)(II) mRNA was detected by RT-PCR in the overlying epidermal layer but not in the dermal layer prepared from the lesional skin of pilomatricoma. The neutral salt-soluble proteins extracted from the tumor of pilomatricoma induced proalpha(1)(II) mRNA in the cultured human keratinocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…We have previously reported type II collagen accumulation in the overlying dermo-epidermal junction (DEJ) of pilomatricoma which is mediated by BMPs 2 and 4 produced by SCs of pilomatricoma. 11 In the present study, we extended our studies to a large number of hair follicle-related tumors including pilomatricoma, trichilemmoma, trichoepithelioma, trichofolliculoma, and CMT, and found type II collagen deposition in the overlying DEJ and tumor cell components as well as BMP expression in tumor cells in pilomatricoma and CMT. Because it has been shown that cultured keratinocytes are induced to express type II collagen by BMP in vitro, the BMPtype II collagen interaction may commonly operate in two distinct benign tumors.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…We have previously reported type II collagen accumulation in the overlying dermo-epidermal junction (DEJ) of pilomatricoma which is mediated by BMPs 2 and 4 produced by SCs of pilomatricoma. 11 In the present study, we extended our studies to a large number of hair follicle-related tumors including pilomatricoma, trichilemmoma, trichoepithelioma, trichofolliculoma, and CMT, and found type II collagen deposition in the overlying DEJ and tumor cell components as well as BMP expression in tumor cells in pilomatricoma and CMT. Because it has been shown that cultured keratinocytes are induced to express type II collagen by BMP in vitro, the BMPtype II collagen interaction may commonly operate in two distinct benign tumors.…”
supporting
confidence: 59%
“…We, for the first time demonstrated that type II collagen was detected in the SCs as well as in the overlying DEJ of pilomatricoma. In our previous article, we focused type II collagen expression in the overlying DEJ of pilomatricoma 11 and were not aware of type II collagen in tumor component of pilomatricoma. Because double immunofluorescence study on the BMP þ /SC þ cases of pilomatricoma revealed that some SCs were double-labeled with both antitype II collagen and anti-BMP antibodies (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations